THE ROLE OF THE ADIWIYATA PROGRAM IN SHAPING STUDENTS' CHARACTER AT MAN 1 PONOROGO - Muhammad Imam Safi’i; Katni; Ayok Ariyanto; Muhammad Azamuddin Syahapala; Sahril Dwi Pamungkas (LPPM STAI Muhammadiyah Probolinggo, 2025)
Allah SWT created the universe, including the Earth with all its contents such as plants and animals, long before the existence of humans. Therefore, humans have an obligation to love and preserve the environment so that it functions according to its nature for the welfare of all. One effort to preserve the environment is manifested through the Adiwiyata program in schools, which aims to build students' character. This study focuses on MAN 1 Ponorogo, a nationally acclaimed madrasah participating in the Adiwiyata program. The goal is to understand the implementation of the program and its role in shaping students' morals. Using qualitative methods through interviews, observations, and documentation, this study shows significant results. The implementation of the Adiwiyata program at MAN 1 Ponorogo successfully encourages students' creativity in waste management, energy and water conservation, as well as the utilization of organic products. More importantly, this program has been proven to be highly influential in shaping students' character. From being previously indifferent, students have become more responsible, independent, and highly aware of the importance of protecting and saving the environment.